2007
DOI: 10.1212/01.wnl.0000268250.10171.b3
|View full text |Cite
|
Sign up to set email alerts
|

How migraines impact cognitive function

Abstract: Migraineurs, specifically those with aura, exhibited less decline on cognitive tests over time vs nonmigraineurs. For the Mini-Mental State Examination, these effects were only apparent among those who were older than 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
3
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 33 publications
4
103
3
12
Order By: Relevance
“…26 Somewhat unexpectedly, the Baltimore Epidemiologic Catchment Area Study reported recently that migraineurs, specifically those with aura, had less decline on cognitive tests over time than nonmigraine patients. 27 This finding occurred in those older than 50 years of age. The authors speculated that certain types of medication commonly used to treat migraine might explain, at least in part, the protective effect in this group.…”
Section: Migraine: a Threat To Cognition?mentioning
confidence: 90%
“…26 Somewhat unexpectedly, the Baltimore Epidemiologic Catchment Area Study reported recently that migraineurs, specifically those with aura, had less decline on cognitive tests over time than nonmigraine patients. 27 This finding occurred in those older than 50 years of age. The authors speculated that certain types of medication commonly used to treat migraine might explain, at least in part, the protective effect in this group.…”
Section: Migraine: a Threat To Cognition?mentioning
confidence: 90%
“…The authors acknowledge that only a limited sample of tests has been performed and that differences in specific domains are not excluded. The second study is part of the Baltimore Epidemiologic Catchment Area Study [44]. Longitudinal data were obtained from waves III (1993)(1994)(1995)(1996) and IV (2004IV ( -2005 of this study regarding cognitive functioning in migraine patients.…”
Section: Migraine and Cognitive Functionmentioning
confidence: 99%
“…Several studies investigated the effects of migraine headaches on cognitive functions. Migraine had been shown as a risk [49] or on the contrary as a protective factor [50] for the impairment of cortical brain function. A relation between migraine and cognitive dysfunction had also been suggested by MRI studies showing that WMLs were more apparent in migraine patients compared with controls [7,51].…”
Section: Discussionmentioning
confidence: 99%